PEMANFAATAN YOUTUBE SEBAGAI MEDIA AJAR UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR - Limarandani, Ni Putu; Patera, A A Aditya Kusuma; Kansil, Margie Candia; Patera, AA Ketut (Telkom University, 2025)
YouTube, as one of the most popular social media platforms among the public, holds significant potential as an educational tool. In the context of education, YouTube can be utilized as a teaching medium, believed to enhance students' interest and motivation in learning. This research identifies how students perceive the utilization of YouTube as a learning tool for Public Speaking skills. Furthermore, the study analyzes the extent to which YouTube's use as an educational medium contributes to increasing students' interest and motivation in learning Public Speaking. The research employs an explanatory research method with descriptive and verificative approaches. Descriptive research aims to provide a clear overview of the research object, while verificative research aims to test hypotheses. The author utilizes t-tests to test hypotheses in this study. Statistical analyses, such as regression, correlation, and determination, are conducted using SPSS software for Windows 20 after performing classic assumption tests including normality, autocorrelation, multicollinearity, and heteroskedasticity tests. The findings indicate that the use of YouTube as an educational medium positively and significantly influences students' learning interest and significantly enhances their learning motivation at a 95% confidence level.